FORMATION OF LINGUISTIC COMPETENCE OF STUDENTS OF FACULTY OF CIVIL ENGINEERING AND ARCHITECTURE (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article discusses the problems of preparing students of Civil Engineering. Problems are noted in the organization of classroom and independent work of students, in the field of assessment and control, as well as educational and methodological tools and teaching methods. The role of a foreign language in the training of future specialists in the field of construction, the causes of reducing the quality of training are reduce the period of renovation of information, its obsolescence even before the completion of the education cycle; changes in the labour market priorities, where different kinds of specialists are required are noted. Conclusions are drawn about the effectiveness of the interaction between traditional and innovative educational concepts in teaching a foreign language in technical universities.